Analysis of melting behavior of layered different phase change materials for a cylinder insert into a channel - Öztop, Hakan Fehmi; Akbal, Omer; Biswas, Nirmalendu; Selimefendigil, Fatih (Elsevier, 2024)
Phase change materials (PCMs) have diverse fields of application due to higher thermal inertia. The present study explores the melting behavior in dual-layered different PCMs in a cylindrical lithium-ion battery module placed in a long channel under the hot air stream. The main cylinder is packed with paraffin wax and covered PCM is chosen as calcium chloride hexahydrate (CaCl2-6H(2)O). The material between two PCMs is considered highly conductive and impermeable. The involved mathematical equations in two-dimensional forms are numerically simulated the applying the finite volume technique. The primary important parameters of melting behavior are the difference in temperature and inlet air velocity. The analysis is carried out for the effective parameters such as the inlet air temperature ( T-hot = 100 degrees C and 120 degrees C) and air velocity (U-air = 2.5 and 5.0 m/s). The results revealed that an increase in air velocity reduces the highest and average temperature of the PCM. The changes in melting time of PCMs decline with time. Higher inlet air temperature also causes fast melting of the PCMs over time. The analysis revealed that the application of PCMs is undue when there is no phase change process. The analysis also revealed that an increment in the inlet air velocity causes a decrease in the average temperature. For the same air inlet temperature (T-hot ) higher air velocity leads to a slower rate of the melting process Therefore, melting time is less by similar to 30 % (for the inner layer) and 32 % (for the outer layer) with decreasing air velocity. The findings of this study will help the designer to improve the battery thermal management system by modulating the temperature.
Keywords: Dual layers; Phase Change Material (PCM); Channel; Melting; Heat transfer